Study Of Wettability And Corrosion Behavior Of Sn-37pb, Sn-8zn-3bi And Sn-3ag-0.5cu Solders - Ridhai, Mohammed Noori (2010)
Lead-based solders have been used extensively for chip-attach and surface-mount processes in the electronic industry, and in marine applications. However, because of toxicity issues related to lead, efforts to develop a cost-effective lead-free replacement have been ongoing. This work investigates the corrosion behavior and resistance of two lead-free solders, namely Sn-8Zn-3Bi and Sn-3Ag-0.5Cu, and compares their performances with a common lead-based solder of Sn-37Pb at ambient temperature. Spreading, wetting angle, shear, and hardness were measured experimentally using standard methods and instrumentations. Experimental results showed that Sn-8Zn-3Bi has the highest wetting angle, while Sn-37Pb demonstrated the highest spreading. Intermetallic compounds Cu6Sn5 were found to be common in Sn-37Pb and Sn-3Ag- 0.5Cu, on the other hand, Cu6Sn8 was detected for Sn-8Zn-3Bi. The highest joint strength was given by Sn-37Pb represented by 0.09 MPa, which is higher by 66% and 33% than those of Sn-8Zn-3Bi and Sn-3Ag-0.5Cu, respectively. However, corrosion after 240 hr in seawater did not affect the magnitudes of shear strength substantially. This outcome was attributed mainly to the short time duration of exposure. Sn-8Zn-3Bi has the highest hardness among all solders. Corrosion caused an increase in hardness of all solders by 3.1, 6.74 and 2.49% for Sn-37Pb, Sn-8Zn-3Bi and Sn-3Ag-0.5Cu respectively.